2020
DOI: 10.1155/2020/2390706
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nigella sativa Supplementation on Oxidative Stress and Antioxidant Parameters: A Meta-Analysis of Randomized Controlled Trials

Abstract: Introduction. Nigella sativa is a commonly used traditional medicine which has been shown to have antioxidant properties. However, its supplementation in patients of clinical trials showed conflicting results. Materials and Method. Relevant articles were searched through PubMed/Medline, SCOPUS, and Google Scholar databases using “Nigella sativa” or “black seed” or “black caraway” or “thymoquinone” and “oxidative stress” or “antioxidant” and “clinical trial” keywords. Randomized, placebo-controlled human interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 29 publications
1
20
1
Order By: Relevance
“…Our meta-analysis showed that the intake of NS seeds resulted in a significant increase in TAC and SOD levels, and also in a significant decrease of MDA levels (which is as an indicator of lipid peroxidation). Consistent with our results, a recent meta-analysis by Ardiana et al (2020) showed that NS supplementation was associated with improved SOD levels but had no significant effect on MDA and TAC levels. However, unlike in our paper, that study did not report data on subgroup analyses.…”
Section: F I G U R Esupporting
confidence: 92%
See 1 more Smart Citation
“…Our meta-analysis showed that the intake of NS seeds resulted in a significant increase in TAC and SOD levels, and also in a significant decrease of MDA levels (which is as an indicator of lipid peroxidation). Consistent with our results, a recent meta-analysis by Ardiana et al (2020) showed that NS supplementation was associated with improved SOD levels but had no significant effect on MDA and TAC levels. However, unlike in our paper, that study did not report data on subgroup analyses.…”
Section: F I G U R Esupporting
confidence: 92%
“…To the best of our knowledge, there are two recent metaanalyses which have reported the beneficial effects of NS on hs-CRP levels (Tavakoly et al, 2019) and oxidative stress parameters (Ardiana et al, 2020). However, none of these studies comprehensively examined the effects of black seed consumption on biomarkers of inflammation and oxidative stress.…”
Section: Ns Contains Several Chemical Ingredients With Pharmacologicalmentioning
confidence: 99%
“…Nigella sativa (NS) is a herbal medicine used in various studies as an alternative medication alongside their chemical counterparts. Several findings suggest that NS oil, obtained from its seeds, maybe a beneficial dietary supplement in preventing and managing various disorders by exerting antioxidative or anti‐inflammatory effects (Ardiana, Pikir, Santoso, Hermawan, & Al‐Farabi, 2020; Hallajzadeh et al, 2020; Tavakoly et al, 2019). It is also indicated that NS might be a suitable choice in managing most of the metabolic parameters, including glycemic homeostasis, lipid profile (Askari et al, 2019; Daryabeygi‐Khotbehsara, Golzarand, Ghaffari, & Djafarian, 2017; Sahebkar, Beccuti, Simental‐Mendía, Nobili, & Bo, 2016), and blood pressure (BP) (Sahebkar, Soranna, et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…TQ treatment has also been shown to reduce oxidative stress markers (superoxide, hydrogen peroxide, and nitric oxide) and attenuate oxidative stress in lipopolysaccharide (LPS)/interferon-gamma (IFNγ) or H 2 O 2 -activated BV-2 microglia by promoting antioxidant enzymes (SOD and CAT), and GSH level, downregulating pro-oxidant genes and upregulating antioxidant genes [ 32 ]. A meta-analysis of five studies using 293 human subjects suggests that black cumin supplementation may have a beneficial role as an antioxidant by improving SOD levels without affecting MDA level and total antioxidant capacity [ 33 ]. With these recent data, it can be concluded that black cumin (in the form of NSO) and its main ingredient TQ have potential antioxidant values that underlie their protective actions against oxidative stress-induced cellular pathology.…”
Section: Benefits Of Black Cumin On Human Health and Disease Conditionsmentioning
confidence: 99%